2020
DOI: 10.3390/healthcare8040409
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Ultra-Short-Term Heart Rate Variability in Military Trainees

Abstract: We aimed to (a) evaluate the agreement between ultra-short-term and criterion resting heart rate variability (HRV) measures in military trainees, and (b) compare associations between HRV recording lengths and body composition. HRV recordings were performed for 10 min in 27 military male students. Mean RR interval, the root-mean square of successive differences (RMSSD), RMSSD:RR interval ratio, standard deviation of normal-to-normal RR intervals (SDNN), and SDNN:RR interval ratio were determined from the last 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…Despite the benefits of HRV testing in health care, the 5-min recording time is impractically long compared with other clinical tests, such as blood pressure measurement and fasting blood sugar, which can be routinely performed in a primary care center or at home. Interest in shorter measurement times prompted researchers to investigate in ultrashort-term HRV test to assess its reliability against short-term tests [1820]. Previous studies that tested the minimum testing time showed a high correlation between ultra-and short-term analyses [79].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the benefits of HRV testing in health care, the 5-min recording time is impractically long compared with other clinical tests, such as blood pressure measurement and fasting blood sugar, which can be routinely performed in a primary care center or at home. Interest in shorter measurement times prompted researchers to investigate in ultrashort-term HRV test to assess its reliability against short-term tests [1820]. Previous studies that tested the minimum testing time showed a high correlation between ultra-and short-term analyses [79].…”
Section: Discussionmentioning
confidence: 99%
“…The use of ultra-short time sequences was investigated in several studies that compared the analysis of ultra-short time measurements with short time measurements demonstrating high correlation between measurements ( 63 65 ). Baek et al ( 66 ) investigated the reliability of this method and concluded that ultra-short time analysis is reliable and comparable to the standard 5-min interval analysis.…”
Section: Methodsmentioning
confidence: 99%
“…HRV metrics were obtained as previously described [ 26 , 27 ]. Three electrodes were placed in a modified lead II configuration with the ground electrode placed at the midpoint of the left clavicle.…”
Section: Methodsmentioning
confidence: 99%
“…From the 15 min recording, a 5 min segment with minimal ectopic beats and artifacts was selected for HRV analysis. Filtering of RR intervals for artifacts and ectopic beats was completed using customized software (LabChart v. 8.1.13 Windows, ADInstruments Pty Ltd., New South Wales, Australia) as previously described [ 26 ]. Time-domain parameters included the mean RR interval (reflects resting heart rate), standard deviation of normal-to-normal RR intervals (SDNN, reflects global variability), and root mean square of successive differences in RR intervals (RMSSD, reflects cardio-vagal control) [ 9 ].…”
Section: Methodsmentioning
confidence: 99%